2021
DOI: 10.1002/ptr.7333
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of herbal treatments for functional dyspepsia: A systematic review and meta‐analysis of randomized clinical trials

Abstract: Functional dyspepsia (FD) is a very common condition globally. Relevant keywords were searched for in title and abstract of selected databases, that is, Medline/ PubMed, Scopus, Embase, Web of knowledge, and Google Scholar. Placebo and active-control trials on herbal remedies amongst adults who were diagnosed with FD were included. Dichotomous outcomes were presented as relative risk (RR) with 95% confidence interval (CI) and continuous outcomes were presented as pooled standardized mean difference (SMD) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…A previous meta-analysis of 29 RCTs suggested that prokinetic agents are more effective than placebo [RR = 0.81; 95% CI: (0.74, 0.89)] [ 48 ]. Eleven [ 28 , 30 – 34 , 37 , 39 , 40 , 42 , 43 ] out of the thirteen RCTs [ 28 , 30 – 34 , 37 , 39 – 44 ] included in this meta-analysis use prokinetics as a control condition, suggesting that the better TER of ZSXP than Western medicine was mainly driven by previous research reporting that herbal medicines have shown efficacy comparable to recognized drugs in treating FD [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis of 29 RCTs suggested that prokinetic agents are more effective than placebo [RR = 0.81; 95% CI: (0.74, 0.89)] [ 48 ]. Eleven [ 28 , 30 – 34 , 37 , 39 , 40 , 42 , 43 ] out of the thirteen RCTs [ 28 , 30 – 34 , 37 , 39 – 44 ] included in this meta-analysis use prokinetics as a control condition, suggesting that the better TER of ZSXP than Western medicine was mainly driven by previous research reporting that herbal medicines have shown efficacy comparable to recognized drugs in treating FD [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of high-quality clinical evidence and there are more adverse events compared to placebo [ 35 , 36 ]. Limited evidence could support that psychotherapy is beneficial for patients with FD [ 37 ]. Herbal remedies might be effective and safe in treating FD and demonstrate comparable effect sizes for efficacy to conventional treatments, [ 38 ] Xiao Yao Pill and modified Ban Xia Xie Xin Decoction probably had great beneficial effect on ameliorating postprandial fullness [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herbal treatments show anti-inflammatory effects and contribute to an improvement in the function of gut microbiota, immune system, central stimuli, and intestinal motility in FD [ 16 ]. A systematic review and meta-analysis of 23 randomized controlled trials (RCTs) comparing the effectiveness of herbal treatments versus a placebo or other standard treatments for FD found that the majority of participants (>60%) in the herbal treatment group experienced an improvement in symptomatology and quality of life, compared to participants in the placebo group [ 17 ]. Chinese herbal medicines have been considered an effective alternative to prokinetics, according to a meta-analysis of 28 RCTs showing that Chinese herbal remedies were more effective than prokinetics at reducing the overall symptoms [ 18 ].…”
Section: Introductionmentioning
confidence: 99%